An ecological study of rushes in pasture : the species observed, the environment and the influence of management in rush control: a thesis presented in partial fulfillment of the requirements for the degree of Master of Science at Massey University - Merry, D. M. E ("Cider") (Massey University, 1934)
The Dominion of New Zealand is dependent on its primary products. There is no need to statistically prove this fact, it is obvious to anyone who troubles to read and think. The marketable value of the Dominion's Dairy Produce, Wool and Frozen Meat, largely determines the economic welfare of the Country. The significant feature is that these primary products are all of grassland origin. Home Consumption of primary products is limited, and the prosperity of the Dominion depends almost entirely on its exportable balance. Attractive markets are distant and competition keen. The marketing of Dominion products suffers disability through distance and transportation, but this is compensated largely by natural climatic advantages, the climate being exceedingly mild and equable, so that de-pasturing of stock may be continued throughout the year on grassland, or with the assistance of supplements of hay and ensilage conserved in springtime from surplus grass growths. It is vitally important that the greatest care and attention should be devoted to maintaining clean and nourishing pasture if increased productivity and incidentally prosperity is to result.
Pg 1 *(Reference by number is to Literature cited). Pg 66 photo missing from original.
Keywords: New Zealand; Juncaceae; Pastures -- Weed control